Novel Genetically Modified Mouse Model to Assess Soman-Induced Toxicity and Medical Countermeasure Efficacy: Human Acetylcholinesterase Knock-in Serum Carboxylesterase Knockout Mice - Marrero-Rosado, Brenda M. (Int J Mol Sci, 2021)
The identification of improved medical countermeasures against exposure to chemical warfare nerve agents (CWNAs), a class of organophosphorus compounds, is dependent on the choice of animal model used in preclinical studies. CWNAs bind to acetylcholinesterase and prevent the catalysis of acetylcholine, causing a plethora of peripheral and central physiologic manifestations, including seizure. Rodents are widely used to elucidate the effects of CWNA-induced seizure, albeit with a caveat: they express carboxylesterase activity in plasma. Carboxylesterase, an enzyme involved in the detoxification of some organophosphorus compounds, plays a scavenging role and decreases CWNA availability, thus exerting a protective effect. Furthermore, species-specific amino acid differences in acetylcholinesterase confound studies that use oximes or other compounds to restore its function after inhibition by CWNA. The creation of a human acetylcholinesterase knock-in/serum carboxylesterase knockout (C57BL/6-Ces1c(tm1.1Loc)AChE(tm1.1Loc)/J; a.k.a KIKO) mouse may facilitate better modeling of CWNA toxicity in a small rodent species. The current studies characterize the effects of exposure to soman, a highly toxic CWNA, and evaluate the efficacy of anti-seizure drugs in this newly developed KIKO mouse model. Data demonstrate that a combination of midazolam and ketamine reduces seizure duration and severity, eliminates the development of spontaneous recurrent seizures, and protects certain brain regions from neuronal damage in a genetically modified model with human relevance to organophosphorus compound toxicity. This new animal model and the results of this study and future studies using it will enhance medical countermeasures development for both defense and homeland security purposes.